HEROES AND OTHERS: RECONSTRUCTING MEMORY AND NATIONAL IDENTITY IN CHINESE WORLD WAR II FILMS - Jiaqi Zheng; Wan Aida Wan Yahaya; Sanghamitra Dalal (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study critically examines the portrayal of Chinese and Japanese images in Chinese World War II films, highlighting their role as tools for reconstructing cultural memory and shaping national identity. Focusing on a corpus of films produced between 1980 and 2010, the paper employs a comparative analytical framework that integrates discourse and semiotic analyses to explore both hero narratives and enemy representations. The findings demonstrate that these films utilize recurring visual and narrative motifs not only to recount historical events, but also to encode symbols of collective trauma and national resilience. Overall, this study underscores the power of Chinese World War II films as dynamic media for the rearticulation of historical narratives and the ongoing construction of national memory and identity.